COLD CHAIN STORAGE AND DISTRIBUTION TECHNOLOGY FOR AGRICULTURAL PRODUCTS IN SAUDI ARABIA - Khan, Razia; Zahir, Roya; Davtyan, Shushan (Yayasan Adra Karima Hubbi, 2025)
This study examines the application of cold chain technology in the storage and distribution of agricultural products in Saudi Arabia, especially in the face of extreme climate challenges and distribution in remote areas. The purpose of the study is to identify the impact of cold chain on product quality, distribution efficiency, and product competitiveness in the international market. The research method used is descriptive-qualitative with data collection through interviews, observations, and secondary data analysis from industry reports and government policies. The results show that the implementation of cold chain reduces the rate of product damage by 30% and increases the export of fresh products, but there is still a gap between urban and rural areas in terms of access to cold chain infrastructure. In conclusion, cold chains play an important role in supporting food security and the sustainability of the agricultural sector in Saudi Arabia, but further infrastructure investment and training are needed to expand its adoption across the country's territory.